Tongue acupuncture for the treatment of post-stroke dysphagia: a meta-analysis of randomized controlled trials - Li, Li; Xu, Fei; Yang, Shengping; Kuang, Peng; Ding, Haoying; Huang, Mei; Guo, Chunyan; Yuan, Zishui; Xiao, Xiao; Wang, Zuhong; Zhang, Pengyue (Frontiers in Neuroscience, 2023)
Objectives Post-stroke dysphagia is the most common neurological impairment after stroke. The swallowing process is controlled by a network made up of the cerebral cortex, subcortical area, and brainstem structure. The disruption of the swallowing network after stroke leads to dysphagia. The affected swallowing muscles after stroke mainly include the laryngeal muscles (suprahyoid muscle and thyrohyoid muscle) and infrahyoid muscle. These muscles experience kinematic effects and muscle strength weakens, resulting in reduced movement in the swallowing process. Acupuncture can change the excitability of cerebral cortical nerve cells, promote the recovery of neurological function, and enhance neuromuscular excitability, ultimately improving the control of swallowing-related nerves and muscles and promoting swallowing functional recovery. In this meta-analysis, we systematically evaluate the clinical efficacy of acupuncture in the treatment of post-stroke dysphagia. Methods Randomized controlled trials of tongue acupuncture therapy for post-stroke dysphagia were searched and selected from seven electronic databases (PubMed, CBM, Cochrane, Embase, CNKI, VPCS, and Wan fang). The Cochrane Collaboration tool was used to conduct methodological quality assessment. Rev. Man 5.4 software was utilized to perform data analysis. Results A total of 15 studies with 1,094 patients were included. Meta-analysis Showed that WST score WST score (MD = −0.56, 95% CI (−1.23, 0.12), Z = 1.62, p < 0.00001), SSA score (MD = −1.65, 95% CI (−2.02, −1.28), Z = 8.77, p < 0.00001). These results suggested that the treatment group (tongue acupuncture or tongue acupuncture combined with other therapies) was superior to the control group in reducing WST scores and SSA scores. The clinical efficacy of the tongue acupuncture group was better compared with the control group (MD = 3.83, 95% CI (2.61, 5.62), Z = 6.88, p < 0.00001). Conclusion The meta-analysis showed that the total effective rate of patients with dysphagia after stroke in the treatment group (acupuncture, tongue acupuncture, and acupuncture combined with other therapy) was higher than that in the control group. These results indicated that acupuncture, tongue acupuncture, and acupuncture combined with other therapy can improve post-stroke dysphagia.